Time-varying multivariate causality among infectious disease pandemic and emerging financial markets: the case of the Latin American stock and exchange markets. Issue 34 (21st July 2022) - Coronado, Semei; Martinez, Jose N.; Romero-Meza, Rafael
ABSTRACT: The purpose of this article is to study the unidirectional causality from the Infectious Disease Equity Market Volatility Tracker (EMV-ID), towards the volatility of five of the most important Latin American stock and Exchange markets. For this, volatility is captured through the DCC-GARCH t-Copula method. In addition, the time-varying Granger multivariate causality test (TV-GC) and the classical Granger causality test (GC) are applied. It is found that, with both methodologies, EMV-ID causes both series, which highlights the importance of having this new indicator for the analysis of the different agents involved in financial markets, among them, regulators, companies and traders in particular. Our results are consistent with the evidence of other research findings about the predictive power of the EMV-ID index on oil price volatility and some European equity markets, and the positive link between EMV-ID and the time-varying of return connectedness across gold, crude oil, world equities, currencies and bonds.